Perjanjian Pembiayaan Konsumen(Studi Tentang Hubungan Hukum Dalam Perjanjian Di PT. Adira DinamikaMulti Finance Tbk. Cabang Purwodadi) - Fauzi, Ghufira All, Kelik Wardiono, S.H., M.H, Inayah, S.H., M.H (2016)
PT. Adira Dinamika Multi Finance Tbk. is a finance company that is in demand by the people of Indonesia. Forms of legal relationships the company uses the principle of freedom of contract. The study was based on doctrinal research with this type of research Legal discovery, the research object is financing agreement PT. Adira Dinamika Multi Finance Tbk. Branch Purwodadi. The basis for the financing agreement PT. Adira Dinamika Multi Finance Tbk. there are some elements of the subject, object, rights and obligations of the parties in accordance/not in accordance with Presidential Decree No. 9 of 2009.